2020
DOI: 10.1002/jcp.29723
|View full text |Cite
|
Sign up to set email alerts
|

A robust six‐miRNA prognostic signature for head and neck squamous cell carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) remains a major health problem worldwide. We aimed to identify a robust microRNA (miRNA)‐based signature for predicting HNSCC prognosis. The miRNA expression profiles of HNSCC were obtained from The Cancer Genome Atlas (TCGA) database. The TCGA HNSCC cohort was randomly divided into the discovery and validation cohort. A miRNA‐based prognostic signature was built up based on TGCA discovery cohort, and then further validated. The downstream targets of prognostic miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Although a significant progress on the pathogenesis of HNSCC has been made in the past decades, the exact molecular mechanisms are still not well understood. Increasing evidences implicates that dysregulation of miRNAs has a critical role in the development and progression of HNSCC (4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Although a significant progress on the pathogenesis of HNSCC has been made in the past decades, the exact molecular mechanisms are still not well understood. Increasing evidences implicates that dysregulation of miRNAs has a critical role in the development and progression of HNSCC (4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…microRNA-1229-3p (miR-1229-3p) has abnormal expression and prognostic significance in gastric cancer [ 15 ], as well as in head and neck squamous cell carcinoma [ 16 ]. Cao et al reported that the function of circ_0037251 knockdown in glioma was achieved by inhibiting the binding of miR-1229-3p and the 3′-untranslated region (3′-UTR) of mTOR [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…There were many models for studying differential methylation of DNA or differential expression of lncRNAs, but there is still a lack of research linking DNA methylation with lncRNAs expression. For instance, Zhao et al, constructed a robust microRNA (miRNA)-based signature for predicting head and neck squamous cell carcinoma (HNSCC) prognosis use expression data [ 37 ]. Shen’s team established 11 differential lncRNAs expression prognostic model for breast cancer [ 38 ].…”
Section: Discussionmentioning
confidence: 99%